Active Learning Strategies for Biodiversity Science - Chodkowski, Nicole; O’Grady, Patrick M.; Specht, Chelsea D.; Zamudio, Kelly R. (Frontiers in Education, 2022)
Organismal courses are inherently integrative, incorporating concepts from genetics, physiology, ecology and other disciplines linked through a comparative and phylogenetic framework. In a comprehensive organismal course, the organisms themselves are a lens through which students view and learn major concepts in evolutionary biology. Here, we present the learning goals of five core concepts (phylogenetics, biogeography, biodiversity, evo-devo, and key traits) we are using to transform organismal courses. We argue that by focusing on organismal knowledge and authentic examples, students learn foundational concepts and investigate biological hypotheses through the content that is unique to individual organismal groups. By using active learning strategies to teach core concepts, instructors can promote an inclusive classroom designed to engage students from diverse backgrounds and facilitate mastery and retention of core biological concepts. This paper provides justification for why organismal biology needs to be kept as part of the biology curriculum, outlines the framework we are using to transform organismal courses, and provides examples of different ways instructors can incorporate active learning strategies and in-class activities in organismal courses in ways that enable their application to further investigation of both foundational and translational sciences for students.